2015
DOI: 10.2807/1560-7917.es2015.20.25.21169
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological investigation of MERS-CoV spread in a single hospital in South Korea, May to June 2015*

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(119 citation statements)
references
References 3 publications
6
112
0
1
Order By: Relevance
“…In the recent outbreak in South Korea, substantial transmission was reported in health care facilities. 98,99 For example, a hospital reported a single primary case, 25 secondary cases, and 11 tertiary cases. 98 HCP have been at high risk of acquiring MERS.…”
Section: Infection Control Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent outbreak in South Korea, substantial transmission was reported in health care facilities. 98,99 For example, a hospital reported a single primary case, 25 secondary cases, and 11 tertiary cases. 98 HCP have been at high risk of acquiring MERS.…”
Section: Infection Control Issuesmentioning
confidence: 99%
“…98,99 For example, a hospital reported a single primary case, 25 secondary cases, and 11 tertiary cases. 98 HCP have been at high risk of acquiring MERS. Al-Tawfiq and Perl reported that of 952 cases reported in Saudi Arabia (June 2012-September 2014), approximately 27% were HCP.…”
Section: Infection Control Issuesmentioning
confidence: 99%
“…While the assumption may be common among modelling studies, it did not allow us to account for the variable type and effectiveness of interventions, especially at later generations of cases in each cluster. Secondly, MERS outbreaks have frequently been amplified in healthcare settings [6,19,20], but we limited ourselves to accounting for individual heterogeneity in a general sense. An improvement on this point was difficult, because MERS outbreaks have been seen mostly in healthcare settings without large-scale community transmission.…”
Section: Figurementioning
confidence: 99%
“…A worth mentioning example, is the MERS-CoV outbreak of South Korea, when a single patient managed to infect more than 70 other individuals while being cared for in an emergency room for three days, representing a clear role of a -superspreader‖. 28 Spread of the virus highly presumed to be thru droplet and close contact of an infected MERS-CoV individual. To witch, the US Center for Disease Control and Prevention (CDC) urged the use appropriate personal protective equipment (PPE) to prevent the transmission among both patients and healthcare providers.79Other potential ways of MERS-CoV spread have been suggested through air borne transmission and/or fomite transmission.…”
Section: Human To Human Transmissionmentioning
confidence: 99%